PROMOTING MULTIMODAL LITERACY THROUGH OBSERVATIONAL INSIGHT - Novitasari, Dwiana; Thoyyibah, Elok Abidatu; Hafshoh, Selzhafani (Jurnal Bahasa Lingua Scientia, 2025)
This article examines the implementation of multimodal literacy in a school setting, specifically through an observational study conducted at MAU Jabal Noor Trenggalek. Multimodal literacy, which incorporates text, visuals, audio, and interactive media, is increasingly important in today's digitally connected world. While existing theories emphasize its significance, a gap remains in its practical integration within the classroom. This study aims to investigate how multimodal literacy is applied in teaching descriptive texts and to identify challenges and opportunities for its effective implementation. Employing a qualitative research design with a case study approach, data were collected through classroom observations, teacher interviews, and analysis of teaching materials. The findings reveal that while multimodal approaches enhance students' engagement and comprehension, issues such as insufficient teacher training, limited access to technology, and inadequate resource allocation were identified as significant barriers. Based on the results, this study recommends targeted professional development, enhanced infrastructure, and culturally relevant teaching materials to integrate multimodal literacy into classroom practices, emphasizing a balanced approach to pedagogy and technology. These insights contribute to the broader discourse on enhancing literacy education in a digital era.